A silver-catalyzed stereoselective domino cycloisomerization–vinylogous aldol reaction of ortho-alkynylbenzaldehydes with 3-alkylidene oxindoles: an entry to functionalized isochromenes. Issue 96 (19th November 2020) - Kumar, Krishna; Singh, Bhuvnesh; Singh, Ravi P.
Abstract : An AgBF4 -catalyzed domino cycloisomerization–vinylogous aldol addition sequence on a multifunctional substrate such as ortho -alkynylbenzaldehydes yielding functionalized 1 H -isochromenes in a single step in high yield and excellent diastereoselectivity (>19 : 1) is described. Abstract : A silver tetrafluoroborate catalyzed domino cycloisomerization–vinylogous aldol addition sequence on a multifunctional substrate such as ortho -alkynylbenzaldehydes yielding functionalized 1 H -isochromenes in a single step with high yield and excellent diastereoselectivity (>19 : 1) is described. The reaction was well tolerated by alkyl, aryl, and unsubstituted alkynylbenzaldehydes, and furnished selective 6- endo -dig adducts exclusively without loss in the regio- as well as diastereoselectivity.